Analisis efisiensi pemasaran padi di Desa Banyubesi Kecamatan Tragah Kabupaten Bangkalan - Ach Wildan Rojabi; Resti Prastika Destiarni (Agriscience, 2026)
Rice as a major food commodity has a very high strategic value, so serious handling is needed to increase its productivity. In addition to increasing productivity, things that need to be considered are also increasing its marketing efficiency. This study aims to analyze the efficiency of rice marketing in Banyubesi Village, Tragah District, Bangkalan Regency. Problems faced by farmers include low rice selling prices due to low grain quality and long distribution channels. This study uses a descriptive quantitative approach with a snowball sampling technique on 30 farmers as respondents. Primary data were collected through interviews using questionnaires. The results of the study indicate that there are two main marketing channels: (1) farmers–middlemen–industry and (2) farmers–rice mills–factories. Analysis of marketing margins, farmer’s share, and marketing efficiency shows that the first channel is more efficient, with a marketing margin of Rp 250/kg and a farmer’s share of 96%. Meanwhile, the second channel has a margin of Rp ±200/kg and a farmer’s share of 60%. The recommendation from this study is the need to increase farmer capacity in post-harvest management and cooperation between farmers to reduce distribution costs to increase marketing efficiency.